2013
DOI: 10.3389/fnhum.2013.00615
|View full text |Cite
|
Sign up to set email alerts
|

Looking for trouble: a description of oculomotor search strategies during live CCTV operation

Abstract: Recent research has begun to address how CCTV operators in the modern control room attempt to search for crime (e.g., Howard et al., 2011). However, an often-neglected element of the CCTV task is that the operators have at their disposal a multiplexed wall of scenes, and a single spot-monitor on which they can select any of these feeds for inspection. Here we examined how 2 trained CCTV operators used these sources of information to search from crime during a morning, afternoon, and night-time shift. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…This measure was termed the 'salience measure', since we assumed that when the observers were all looking at the same visual point at the same time, this would correspond to a salient event in the clip (e.g. Sawahata et al, 2008;Smith and Mital, 2013;Stainer et al, 2013). After each clip was shown during the eye-tracking experiment, the participant was asked to rate the likelihood that a violent incident occurred after it ended, using a six-point scale that ranged from 1 (extremely unlikely) to 6 (extremely likely).…”
Section: Design and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…This measure was termed the 'salience measure', since we assumed that when the observers were all looking at the same visual point at the same time, this would correspond to a salient event in the clip (e.g. Sawahata et al, 2008;Smith and Mital, 2013;Stainer et al, 2013). After each clip was shown during the eye-tracking experiment, the participant was asked to rate the likelihood that a violent incident occurred after it ended, using a six-point scale that ranged from 1 (extremely unlikely) to 6 (extremely likely).…”
Section: Design and Proceduresmentioning
confidence: 99%
“…However, to be effective, this application of CCTV requires a human operator to be able to identify the presence of hostile intentions from only visual cues in complex scenes (Howard et al, 2011a;Howard et al, 2011b;Howard et al, 2009;Stedmon et al, 2008;Troscianko et al, 2004). The amount of visual information and the number of actions these operators monitor every day is very high, and this makes these individuals optimal subjects for examining how extensive experience in the visual analysis of behavior in real-world scenes affects human brain function.…”
Section: Introductionmentioning
confidence: 99%
“…For work and entertainment purposes we view content on screens for much of the time and many of the environments that we find ourselves in during everyday life contain screens. Indeed there are tasks that we perform that rely on screen-based viewing like CCTV surveillance (Stainer, Scott-Brown, & Tatler, 2013). Thus screen-based viewing paradigms can be informative of certain everyday behaviours.…”
Section: Paradigmatic Considerationsmentioning
confidence: 99%
“…less) experienced operator utilising the spot monitor more often. Stainer et al (2013) identified that their observers selectively allocated attention based on expected informativeness. This replicated Howard, Troscianko, and Gilchrist's (2010) finding that participants with more experience watching football matches shifted their eyes to more informative areas of the footage earlier than did non-experienced observers.…”
mentioning
confidence: 99%
“…Howard, Troscianko, Gilchrist, Behera, and Hogg (2009) stated that measuring eye movements during CCTV monitoring might produce innovative data to determine the strategies people use when attending to footage. Stainer, Scott-Brown, and Tatler (2013) examined the eye movements of two trained CCTV operators monitoring multiple display screens on a wall, compared to a single-spot monitor (the operator could select only one of multiple screens to inspect in more detail). They found that more attention was allocated to the single-screen-spot monitor than the multiplex display, with the more (cf.…”
mentioning
confidence: 99%